Influence of the Mediterranean diet on seminal quality—a systematic review - Piera-Jordan, Clara Ángela; Prieto Huecas, Laura; Serrano De La Cruz Delgado, Verónica; Zaragoza Martí, Ana; García Velert, María Belén; Tordera Terrades, Cristina; Sánchez-SanSegundo, Miriam; Hurtado-Sánchez, José Antonio; Tuells, José; Martín Manchado, Laura (Frontiers in Nutrition, 2024)
Currently, there is a growing interest in the study of fer5lity because fer5lity-related problems affect up to 15% of the world's popula5on.The aim of this study was to know the influence of the Mediterranean diet on seminal quality in men of reproduc5ve age. For this purpose, a systema5c review of the literature was carried out following the PRISMA method.Electronic searches were carried out in the interna5onal databases PubMed, Scopus, the Cochrane Library, and Web of Science. 10 ar5cles with 2032 men were included. As inclusion criteria, ar5cles published between 2012 and 2022 were selected and ar5cles that included men aged between 18 and 55 years. Nutri5onal status was assessed through weight, height and BMI. Dietary habits were evaluated through different indexes and food frequency ques5onnaires and finally semen quality was evaluated by measuring sperm concentra5on and mo5lity (progressive and non-progressive).In 6 (60%) of the included ar5cles a posi5ve rela5onship between adherence to the Mediterranean diet and semen quality was demonstrated, in 2 (20%) of the ar5cles no associa5on was found and finally, in 2 (20%) of the included ar5cles the rela5onship between dietary pa^erns typical of DM and semen quality was evaluated.Dietary habits influence semen quality. Adherence to the Mediterranean diet can improve male reproduc5ve health as it is a diet with an5oxidant and an5-inflammatory effects. This is the first systema5c review about the influence of the Mediterranean diet on semen quality, being the results posi5ve. These findings may allow us to provide be^er advice to our pa5ents and to establish interven5ons with the aim of improving the results in assisted reproduc5on techniques.